Asuhan Keperawatan Keluarga Pada Tn. M Keluarga Tn. M Dengan Gangguan Sistem Persyarafan : Stroke Hemoragik Di Desa Purwodadi RT 02 RW 04 Kecamatan Tonjong Kabupaten Brebes - Adinda Arini Annisa; Esti Nur Janah; Siti Fatimah (STIKES Columbia Asia Medan, 2025)
Stroke is a neurological disorder that often causes severe complications, including physical and cognitive impairments. Family involvement is essential in the recovery process, especially in home-based care. This case study aims to describe the application of family nursing care to a patient with hemorrhagic stroke in Purwodadi Village, Tonjong District, Brebes Regency. Data collection methods included interviews, observations, physical examinations, and nursing documentation using the SOAP format. The intervention focused on family support in mobilization, Range of Motion (ROM) exercises, and health education. The results showed an increase in family knowledge and participation, and improvements in the patient's mobility and self-care abilities. This study confirms that family-centered nursing care is effective in improving the quality of recovery and should be integrated into community nursing practice.